The Description of Future Bride Nutritional Status Included Incidence of Anemia, Chronic Energy Deficiency (CED), and Nutritional Status Based on Body Mass Index - Nonik Ayu Wantini; Lenna Maydianasari; Agnes Savitri Agni (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2023)
Currently, Indonesia is still facing reproductive health problems which are marked by the high maternal mortality rate (MMR) and infant mortality rate (IMR). The low status of public health, especially women's health, is influenced by various factors. One of the factors is nutritional status. Comprehensive intervention through the continuum of care approach is important to be carried out more upstream, namely during the preconception period (future bride). Examination of the nutritional status of the bride aims to detect early problems of underweight, overweight and micronutrient deficiencies (anemia). Optimal nutritional status before pregnancy is a form of readiness for a healthy pregnancy. The purpose of this study was to describe nutritional status (incidence of anemia, chronic energy deficiency (CED), and nutritional status based on body mass index). The method of the study was descriptive quantitative. The sample for this study was 76 brides-to-be who visited the Berbah Health Center for the period August-October 2022, and were selected by purposive sampling. The data obtained was secondary data obtained from medical records. The results showed that 61.8% of women’s health status was poor (one of the 3 nutritional status indicators was not in the normal category). Incidence of anemia 28.9%, chronic energy deficiency 15.8%, overweight and obesity 22.4%, very thin and thin 34.2%. Conclusion: the prevalence of problems with the nutritional status of the bride is still high. Further studies related to the causes of nutritional problems in future brides are needed